Cultura constitucional - Raoni Macedo Bielschowsky (2016)
The Theory of Constitution appears in the Weimar Constitution context, with the debates of the 1920s, and early 1930s, about the Theory of the State, the Law of the State and the German Constitution itself. The very start was the Kelsenian formulation that was followed by different answers including those ones characterized by a dialectical perspective of the constitutional phenomenon, which are very important to the comprehension of the democratic Rechtsstaat . With them, there were a special attention to the issues of legitimacy, validity and efficacy of Constitution, especially, to the relation between them. The approach to the constitutional experience since the key constitutional culture intents to evidence these relations from three basic dimensions: the identity of the constitutionalism, the constitutional identity and the culture of constitution. With them it is assumed that an order intended as constitutional bases its own legitimacy on a particular Western identity very identified with constitutionalism, which demands the articulation between local identities and cultures, conforming and building a very new and unique reading: a new constitutional identity. This one is never completely ready or finished, it becomes alive at the very same time that it is lived, constructed, deconstructed and reconstructed in and by the juridical-political community. An identity that reflects this collectivity at the same time it proposes itself as a normative project to it, demanding tasks and transformations to the community. Therefore, the possibility of such tasks has as central topic the consolidation and the reaffirmation of a culture of constitution, linked to these two identities, the broader one of the constitutionalism and the narrower one of a constitutional identity, which is the internal guarantee of efficacy and effectiveness of a Constitution. Hence, a constitutional order has its effectiveness rather linked to the strengthening and often reconciliation of its legitimacy in the community. In these terms it is possible to affirm that the Constitution stands as a cultural unit, integrant and integrated, of the community and its citizens.